Biological kinship analysis in extremely critical samples: The case of a Spanish Neolithic necropolis. (December 2017) - Gomes, Cláudia; Gibaja, Juan F.; Buxó, Jordi Roig I.; Baeza-Richer, Carlos; López − Matayoshi, César; López-Parra, Ana María; Palomo-Díez, Sara; Subirà, M. Eulàlia; Arroyo-Pardo, Eduardo
Abstract: It is common in archeology and some forensic cases to make assumptions about the relationship between persons buried in the same grave, or in distinct burials but in the same cemetery. However, there is no objective criterion to make such suppositions. This study aims to investigate the biological relationship among six Neolithic individuals (4200–3400 cal BC) from the Can Gambús-1 necropolis (Barcelona, Spain) as well as, their possible mitochondrial ancestry. From at least 47 tombs, six skeletons were selected, from six individual graves, selecting from each one three integral teeth, without cavities or caries. To carry out this study, the samples were analyzed by two distinct extraction methods, one destructive and other non-destructive, and to determine a presumptive (biological) kinship between the buried individuals, small length nuclear DNA markers were considered, as well as a mitochondrial DNA analysis, in order to determine their maternal lineage. The samples were extremely degraded, requiring several attempts to achieve sequences with a standard quality, without double peaks or other artefacts. Despite the degraded state of the samples, it has been possible to analyze the mitochondrial information and to determine that the studied individuals had a European ancestry, and were not maternally related, since they did not share the same mitochondrial haplotype.